Strategic IT Alignment with Business Strategy: Service Oriented Architecture Approach - Mohammad, Abdi; Dominic P, Dhanapal Durai (2010)
Abstract—Enterprises are moving fast to transform into service orientation to maintain their competitive advantage. In order to meet rapidly changing demands, and achieve true agility an enterprise needs strategic IT alignment with business strategy integrated with Service Oriented Architecture (SOA). As enterprises transform service oriented enterprises, the use of IT to meet customer demands becomes an important research issue. The primary aim of this paper is to develop a model which explains the interplay between strategic alignment dimensions of governance, communication, and architecture enabled by SOA, and enterprise agility. The model was tested using survey data collected from 202 Malaysian service industries. The data was analyzed using structural equation modeling AMOS 5 to test the model fit. Using maximum likelihood estimation analysis, the model fit for data was achieved. The key results were that the factors of alignment via governance, alignment via communication, and alignment via architecture are good predictors for enterprise agility.